Althochdeutsche Dialekte – Neuhochdeutsche Dialekte. Terminologische Probleme bei Beschreibungen älterer Sprachzustände. - Morciniec, Norbert (Studia Germanica Posnaniensia, 2018)
In the history of the German language of the period between 750–1050, the term “Old High German dialects” is used to characterize the Franconian, Bavarian and Alemannic languages, in which the records from this period are written. The author of the article analyses the meaning of the term in question and explains why the languages of those records have been called “dialects” (despite the fact that the common language, whose dialects they might have been, did not exist at that time yet), and on what grounds they have been called “German” dialects (though the German nationality did not exist at that time either).